Development of Environmentally Friendly Nano Photosensitizers from Zn-Catharanthus roseus and Cu-Catharanthus roseus Complexes for Dye-Sensitized Solar Cells - Qoriati, Yani; Al-Bari, Akhmad; Februyani, Nawafila (Proceeding International Conference on Religion, Science and Education, 2026)
Dye-sensitized solar cells are a promising renewable energy technology that offers an environmentally friendly alternative source of electricity. One of main components of DSSCs is photosensitizer, which functions to absorb light and convert it into electrical energy. Use of natural-based photosensitizers, such as plant extracts from Catharanthus roseus, offers advantages in terms of sustainability and environmental friendliness. Nano sized photosensitizers based on transition metals such as zinc (Zn) and copper (Cu), combined with active compounds from Catharanthus roseus extract, can enhance properties of photosensitizer, particularly in light absorption and electron transfer efficiency. However, type of metal used in the nano photosensitizer Zn or Cu can have a significant impact on performance of solar cell, especially in terms of energy conversion efficiency and stability. This study aims to examine effect of different nano-photosensitizers, Zn-Catharanthus roseus and Cu-Catharanthus roseus, on performance of dye-sensitized solar cells. Method used includes ultrasonic-assisted extraction of Catharanthus roseus leaves using ethanol as the solvent. Nano-photosensitizers of Zn and Cu were then synthesized in equal ratios. Synthesized nano-photosensitizers were applied to TiO2 electrodes as working electrode, with Pt used as the counter electrode in DSSC assembly. Efficiency testing was carried out using a halogen lamp as light source. The results showed that difference between the Zn-Catharanthus roseus and Cu-Catharanthus roseus nano-photosensitizers affected efficiency of the dye-sensitized solar cells. Highest efficiency was obtained using the Zn-Catharanthus roseus photosensitizer, with a value of 4.97 × 10-3 %, indicating that Zn-Catharanthus roseus has strong potential as a photosensitizer for dye-sensitized solar cells.